Differing House Finch Cytokine Expression Responses to Original and Evolved Isolates of Mycoplasma gallisepticum - Vinkler, Michal; Leon, Ariel E.; Kirkpatrick, Laila; Dalloul, Rami A.; Hawley, Dana M. (Frontiers in Immunology, 2018)
The recent emergence of the poultry bacterial pathogen Mycoplasma gallisepticum (MG) in free-living house finches (Haemorhous mexicanus), which causes mycoplasmal conjunctivitis in this passerine bird species, resulted in a rapid co-evolutionary arms-race between MG and its novel avian host. Despite extensive research on the ecological and evolutionary dynamics of this host-pathogen system over the past two decades, the immunological responses of house finches to MG infection remain poorly understood. We developed seven new probe-based one-step RT-qPCR assays to investigate mRNA expression of house finch cytokine genes (IL1B, IL6, IL10, IL18, TGFB2, TNFSF15 and CXCLi2, syn. IL8L). These assays were then used to describe cytokine transcription profiles in a panel of 15 house finch tissues collected at three distinct time points during MG infection. Based on initial screening that indicated strong pro-inflammatory cytokine expression during MG infection at the periorbital sites in particular, we selected two key house finch tissues for further characterization: the nictitating membrane, i.e. the internal eyelid in direct contact with MG, and the Harderian gland, the secondary lymphoid tissue responsible for regulation of periorbital immunity. We characterized cytokine responses in these two tissues for sixty house finches experimentally inoculated either with media alone (sham) or one of two MG isolates: the earliest known pathogen isolate from house finches (VA1994) or an evolutionarily more derived isolate collected in 2006 (NC2006), which is known to be more virulent. We show that the more derived and virulent isolate NC2006, relative to VA1994, triggers stronger local inflammatory cytokine signalling, with peak cytokine expression generally occurring three to six days following MG inoculation. We also found that the extent of pro-inflammatory interleukin 1 beta signalling was correlated with conjunctival MG loads and the extent of clinical signs of conjunctivitis, the main pathological effect of MG in house finches. These results suggest that the pathogenicity caused by MG infection in house finches is largely mediated by host pro-inflammatory immune responses, with important implications for the dynamics of host-pathogen co-evolution.